KAJIAN FISHING GEAR SERTA METODE PENGOPERASIAN RAWAI (LONG LINE) DI PERAIRAN BAGIAN SELATAN PULAU TARAKAN - Firdaus, Muhammad; ., Kamelia (Jurnal Harpodon Borneo, 2011)
This Review aims to find fishing gear and methods of longline Operating are generally operating at Southern Ocean Tarakan Island. The method used is descriptive method of collecting data by recording all the elements that become the object of review (literature study), interviews and observations (direct observation). In general, the longline operations at Southern Ocean Tarakan Island is a basic longline (Bottom long line). The method is passive fishing and the principles of fish with bait. The Operating longline method consists of three stages among others the setting (gear reduction), soaking (soaking gear, ± 2 hours) and hauling (withdrawal of fishing gear). Dimensions long line fishing gear the normally operate consists of cork floats (length: 30-40 cm), anchor line (Length: 35 m), ballast line Trailers (weight: 2 kg), the main anchor (weight: 3 kg ), length of the top line (length: 400 m), branch line(length: 50 m), hook No.7 amount 200-300. Keywords :            Fishing gear, methods of longline Operating, at Southern Ocean Tarakan Island.